The Effect of Workload on Effective Education Delivery to Patients in the Cempaka II Inpatient Room, Bandung Adventist Hospital - Aruan, Rohani; Stephen Legoh; Jacqueline Makanoneng (HealthCare Nursing Journal, 2025)
Hospitals play a vital role in healthcare systems by delivering comprehensive medical services. Nurses, as essential healthcare personnel, are responsible for providing holistic nursing care, including health education. However, a high workload may compromise their ability to educate patients effectively.This study aimed to analyze the relationship between nurses’ workload and the effectiveness of patient education in the Cempaka II inpatient ward at Advent Hospital Bandung.A descriptive quantitative design was employed, utilizing univariate and bivariate analysis. Data were collected through structured questionnaires with from 16 nurses and analyzed using frequency distribution and correlation tests.The study revealed that 62.5% of nurses experienced a high workload. Despite this, 62.5% of respondents reported delivering effective patient education. Key workload factors included understaffing, patient dependency, documentation demands, and expectations from hospital leadership and patients’ families.While a majority of nurses provided education effectively, high workload indicators, such as staffing shortages and extensive responsibilities, remained a significant challenge, potentially affecting consistency and depth in patient education delivery.High nurse workload is prevalent and may hinder optimal patient education. Strategies to balance workload and maintain education quality are essential to support patient outcomes.